Transformasi Tafsir Al-Qur’an di Indonesia: Dari Tradisi Klasik Menuju Pendekatan Tematik Kontemporer - Imron Taslim; Halimatussadyah Halimatussadyah; Kusnadi Kusnadi; Pathur Rahman (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the transformation of Qur’anic interpretation in Indonesia, shifting from traditional classical approaches to contemporary thematic approaches. The research aims to analyze the factors influencing this paradigm shift, community preferences towards both approaches, and the resulting social and academic implications. The method employed is qualitative descriptive, combining literature review and surveys involving 650 respondents from university students, Islamic school pupils, and traditional pesantrensantri. The findings reveal that the thematic approach is increasingly favored by academics and Islamic school students, while classical tafsir remains dominant in traditional pesantren. This transformation reflects the need for a more contextual and socially relevant understanding of the Qur’an. This study fills a gap in research concerning the integration of classical and thematic tafsir and provides recommendations for future development in tafsir studies.